1998
DOI: 10.1105/tpc.10.2.219
|View full text |Cite
|
Sign up to set email alerts
|

An Arabidopsis Brassinosteroid-Dependent Mutant Is Blocked in Cell Elongation

Abstract: Cell elongation is a developmental process that is regulated by light and phytohormones and is of critical importance for plant growth. Mutants defective in their response to light and various hormones are often dwarfs. The dwarfed phenotype results because of a failure in normal cell elongation. Little is known, however, about the basis of dwarfism as a common element in these diverse signaling pathways and the nature of the cellular functions responsible for cell elongation. Here, we describe an Arabidopsis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
114
1
5

Year Published

2002
2002
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 291 publications
(124 citation statements)
references
References 43 publications
4
114
1
5
Order By: Relevance
“…bri1 is the only BR-insensitive loss-of-function mutant identified so far by genetic screens (Clouse et al, 1996;Kauschmann et al, 1996;Li and Chory, 1997). Dark-grown bri1 mutants resemble BRdeficient mutants, exhibiting severe dwarfism with dark green epinastic leaves, and reduced apical dominance and fertility (Clouse et al, 1996;Kauschmann et al, 1996;Li et al, 1996;Szekeres et al, 1996;Azpiroz et al, 1998;Choe et al, 1999;Choe et al, 2001;Noguchi et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…bri1 is the only BR-insensitive loss-of-function mutant identified so far by genetic screens (Clouse et al, 1996;Kauschmann et al, 1996;Li and Chory, 1997). Dark-grown bri1 mutants resemble BRdeficient mutants, exhibiting severe dwarfism with dark green epinastic leaves, and reduced apical dominance and fertility (Clouse et al, 1996;Kauschmann et al, 1996;Li et al, 1996;Szekeres et al, 1996;Azpiroz et al, 1998;Choe et al, 1999;Choe et al, 2001;Noguchi et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Until the isolation and characterization of branching mutants in various species, it was not possible to address these issues. In recent decades, many branching mutants have been isolated that have problems with auxin, cytokinin, or brassinosteroids, for example, and show highly pleiotropic phenotypes typical for these hormones (Lincoln et al, 1990;Azpiroz et al, 1998;Tantikanjana et al, 2001). However, a class of mutants were isolated that displayed a specific increase in bud outgrowth that was not correlated with any known hormonal signal (Beveridge et al, 1996(Beveridge et al, , 1997.…”
mentioning
confidence: 99%
“…DWF4 is a C-22-α-hydrolase that catalyzes the rate limiting step of BR biosynthesis (Choe et al 1998). Null dwf4 mutations (Azpiroz et al 1998;Nakamoto et al 2006) are infertile and showed a stronger dwarf phenotype compared to that of axhs1, indicating that axhs1 is a weak allele of DWF4. Nakamoto et al (2006) found that inhibition of BR biosynthesis by either a leaky mutation of DWF4 or Brz rescues defects in tropic responses of hypocotyls in the Arabidopsis nph4(arf7) mutant.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, we carried out a complementation test between axhs1 and dwf4-102. Since strong mutant alleles of DWF4 are infertile (Azpiroz et al 1998;Nakamoto et al 2006), heterozygous dwf4-102 was crossed with axhs1. Analysis of the F1 and F2 segregation indicated that axhs1 is allelic to dwf4-102 ( Figure 3F).…”
Section: Axh1 Is a Weak Allele Of Dwf4mentioning
confidence: 99%